Clinical Outcome of Azithromycin dehydrate used in treatment of acute apical periodontitis and severe chronic marginal gingivitis compared to other antibiotics (Mustansiria Dental Journal, 2018)
Ninety six patient aged between 12 – 50 years attending the college of dentistry ,Al- mustansyria university and the investigators clinics , they were divided into twoequal groups; 48 Patients suffering acute apical periodntitis ( painful ) weresubjected to different antibiotics after drainage and their prognosis towards nonpainfulchronic apical perioddontitis was observed and were as follows : 29.3% withAzithromycin, 20.8 % with ampicilline and 29.3% with ampicilline plusmetronidazole with a total of 79.4 % .The second group, were 48 students aged 12- 20 years suffering from severemarginal gingivitis ( GI-3 ) and were subjected to different antibiotics afterprophylaxis and some of them were kept on prophylaxis alone and their progress tomild marginal gingivitis ( G.I.1) was observed and were as follows :20.8 % withazithromycin , 16.7 % with ampicilline, 22.9 % with ampicilline plus metronidazoleand 20.8 % with prophylaxis and oral hygiene practice alone with a total of 81.2 %showing no significant difference between prophylaxis alone and those withprophylaxis and antibiotics .